Legal and Ethical Analysis of Mystery Box Transactions in E-Commerce Platforms: A Sharia Economic Law Perspective - Iwan Setiawan; Dudang Gojali; Chaerul Shaleh; Mualimin Mochammad Sahid (IAIN Palangka Raya, 2026)
Tier 2 (Indexed by WOS/Scopus/ERA)